2020
DOI: 10.1021/acsomega.0c00122
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Foamlike NiO/CuO Nanocomposites with Superior Catalytic Activity toward the Reduction of 4-Nitrophenol

Abstract: Foamlike NiO/CuO nanocomposites were prepared using a simple electrospinning technique combined with appropriate calcination. By tuning the Ni/Cu molar ratio (1:2, 1:1, and 2:1) in the initial material, different NiO/CuO nanocomposites were obtained. X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), X-ray photoelectron spectroscopy (XPS), and nitrogen adsorption−desorption isotherms were used to characterize the composites. Furthermore, they were investigated as catalysts for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…The photocatalytic degradation properties of samples were evaluated under visible light irradiation ( λ ≥ 420 nm) with RhB as the target pollutant. The degradation curves of RhB by S-TAA, S-TA, S-TSC and S-NS accord with the first-order-kinetic equation: 34 ln( C 0 / C t ) = kt where t and k are the visible light irradiation time and degradation rate constant, respectively. Compared with CdS prepared by many other methods, S-TAA shows superior photocatalytic degradation performance.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The photocatalytic degradation properties of samples were evaluated under visible light irradiation ( λ ≥ 420 nm) with RhB as the target pollutant. The degradation curves of RhB by S-TAA, S-TA, S-TSC and S-NS accord with the first-order-kinetic equation: 34 ln( C 0 / C t ) = kt where t and k are the visible light irradiation time and degradation rate constant, respectively. Compared with CdS prepared by many other methods, S-TAA shows superior photocatalytic degradation performance.…”
Section: Resultssupporting
confidence: 64%
“…The crystallite size of the four samples was obtained by Debye–Scherrer's formula, 34 where D is the crystallite size, k is 0.94, λ is the wavelength of the X-ray radiation (1.5 Å), β is the full width half maximum and θ is the angle of diffraction. The average particle size was 3.2, 17.1, 1.6 and 2.7 nm for S-NS, S-TAA, S-TA, and S-TSC, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For CNM (6 : 1), the TOF was found to be 18.40 molecules g À1 s À1 which is also relatively higher than that of the other catalysts reported. 58,59 The rate constant of the CNM (6 : 1) catalyst was found to be higher compared to other catalysts containing expensive noble metals such as Au, Pd, etc. In comparison with these reported studies, it was found that the rate constant (k, min À1 ) value obtained in the case of CNM (6 : 1) (0.71 min À1 ) was the highest among all the values listed (Table S2, ESI †).…”
Section: Njc Papermentioning
confidence: 96%
“…For CNM (6 : 1), the TOF was found to be 18.40 molecules g −1 s −1 which is also relatively higher than that of the other catalysts reported. 58,59…”
Section: Application In Catalytic Reduction Of Nitrophenol and Dye De...mentioning
confidence: 99%
“…Scientists are continuously trying to improve its reductive activity by doping it with foreign elements or altering reaction conditions. Various 3d/4d transition-metal oxide, such as SnO 2 , CdS, Fe 2 O 3 , ZrO 2 , CuO, TiO 2 , and ZnO have been reported in the reduction of 4-NP to 4-nitroaniline (4-NA) in the presence of NaBH 4 . Among these, ZnO attracts attention due to its low cost, high availability, low toxicity, and high stability and can be easily doped with foreign elements to improve catalytic and photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%